Nilai-Nilai Yang Hidup Dalam Masyarakat (Living Constitution) Dalam Putusan Mahkamah Konstitusi Pada Perkara Pengujian Undang-Undang Nomor 7 Tahun 2004 Tentang Sumber Daya Air - Bening Setara Bulan; Abu Tamrin; Sodikin Sodikin (STAATSRECHT: Indonesian Constitutional Law Journal, 2019)
Abstract.The Constitutional Court is an institution that has the role of the guardian of the constitution. The Constitutional Court must ensure the supremacy of the constitution, and the constitution is carried out consistently in society. As the guardian of the constitusion, the constitutional court is attached to the authority of judicial review. The decision on testing the Law on Natural Resources has two different decisions which are caused by the interpretation of the Constitutional Court judges on Article 33 Paragraph (2), Paragraph (3), and Paragraph (4) of the 1945 Constitution of the Republic of Indonesia. The judge relies on his interpretation of the value of community development, especially to the value of water resources. This on the one hand has resulted in legal uncertainty, but on the other hand it includes the efforts of judges to harmonize the rules of constitutional law as living constitution to be in accordance with the development of society.Keywords: The Living Constitution, RI Constitutional Court